Patient needs and priorities for patient navigator programmes in chronic kidney disease: a workshop report. Issue 11 (5th November 2020) - Guha, Chandana; Lopez-Vargas, P; Ju, Angela; Gutman, Talia; Scholes-Robertson, Nicole Jane; Baumgart, Amanda; Wong, Germaine; Craig, Jonathan; Usherwood, Tim; Reid, Sharon; Cullen, Vanessa; Howell, Martin; et al.
Abstract : Background and objective: Patients with early chronic kidney disease (CKD) face challenges in accessing healthcare, including delays in diagnosis, fragmented speciality care and lack of tailored education and psychosocial support. Patient navigator programmes have the potential to improve the process of care and outcomes. The objective of this study is to describe the experiences of patients on communication, access of care and self-management and their perspectives on patient navigator programmes in early CKD. Design, setting and participants: We convened a workshop in Australia with 19 patients with CKD (all stages including CKD Stage 1 to 5 not on dialysis, 5D (dialysis), and 5T (transplant)) and five caregivers. All of them were over 18 years and English-speaking. Transcripts from the workshop were analysed thematically. Results: Four themes that captured discussions were: lost in the ambiguity of symptoms and management, battling roadblocks while accessing care, emotionally isolated after diagnosis and re-establishing lifestyle and forward planning. Five themes that focussed on patient navigator programmes were: trust and credibility, respecting patient choices and readiness to accept the programme, using accessible language to promote the programme, offering multiple ways to engage and communicate and maintaining confidentiality and privacy. Of the 17 features identified as important for a patient navigator programme, the top five were delivery of education, psychosocial support, lifestyle modification, communication and decision-making support and facilitating care. Conclusion: Patient navigator services can address gaps in services around health literacy, communication, psychosocial support and coordination across multiple healthcare settings. In comparison to the existing navigator programmes, and other services that are aimed at addressing these gaps, credible, accessible and flexible patient navigator programmes for patients with early CKD, that support education, decision-making, access to care and self-management designed in partnership with patients, may be more acceptable to patients.